Dexmedetomidine and fentanyl for epidural analgesia in lower limb orthopedic surgeries: a comparative evaluation - Kumar, Surendra; ., Pravina (International Journal of Advances in Medicine, 2019)
Background: Epidural anesthesia is the most frequently used technique for providing operative analgesia in lower abdominal and limb surgeries. This study aimed at comparative evaluation of dexmedetomidine and fentanyl for epidural anaesthesia in lower limb orthopedic surgeries. Methods: This study was conducted in the department of Anesthesiology and critical care Medicine, MLB Medical College Jhansi. Patients undergoing lower limb orthopaedic surgery aged between 21 to 50 years and belonging to American Society of Anaesthesiologist (ASA) grade 1or 2 were included. Informed and written consent was obtained. Subjects were divided into two groups. Statistical analysis was done using SPSS version 16.0 software. t-test, Chi-square test, and Mann-Whitney tests were applied. Results: Age wise distribution, body weight and mean duration of surgical time was comparable in both groups and found statistically insignificant. Time to achieve sensory level at T10 was found to be significantly less in Group RD as compared to Group RF. Early onset of motor block in Group RD was seen (10.12min) as compared to fentanyl (13.36min). Complete motor block was achieved in significantly lower time by Group RD as compared to Group RF. Duration of motor block was significantly higher in Group RD as compared to Group RF subjects. Better sedation score was found in Group RD. Conclusions: Dexmedetomidine is better as an adjuvant to ropivacaine than fentanyl for epidural anaesthesia because of intense analgesia, better quality of motor block and prolong post-operative analgesia, along with higher sedation scores.